Comparative immunogenicity of decellularized wild type and alpha 1, 3 galactosyltransferase knockout pig lungs. (September 2021) - Gasek, Nathan; Dearborn, Jacob; Enes, Sara Rolandsson; Pouliot, Robert; Louie, Jessica; Phillips, Zachary; Wrenn, Sean; Uhl, Franziska E.; Riveron, Alexander; Bianchi, John; Commins, Scott P.; Delance, Nicole; et al.
Abstract: Decellularized pig lungs recellularized with human lung cells offer a novel approach for organ transplantation. However, the potential immunogenicity of decellularized pig lungs following exposure to human tissues has not been assessed. We found that exposure of native lungs from wildtype and transgenic pigs lacking alpha (1, 3)-galactosyltransferase (α-gal KO) to sera from normal healthy human volunteers demonstrated similar robust IgM and IgG immunoreactivity, comparably decreased in decellularized lungs. Similar results were observed with sera from patients who had previously undergone transcutaneous porcine aortic valve replacement (TAVR) or from patients with increased circulating anti -α-gal IgE antibodies (α-gal syndrome). Depleting anti -α-gal antibodies from the sera demonstrated both specificity of α-gal immunoreactivity and also residual immunoreactivity similar between wildtype and α-gal KO pig lungs. Exposure of human monocytes and macrophages to native wildtype lungs demonstrated greater induction of M2 phenotype than native α-gal KO pig lungs, which was less marked with decellularized lungs of either type. Overall, these results demonstrate that native wildtype and α-gal KO pig lungs provoke similar immune responses that are comparably decreased following decellularization. This provides a further platform for potential use of decellularized pig lungs in tissue engineering approaches and subsequent transplantation schemes but no obvious overall immunologic advantage of utilizing lungs obtained from α-gal KO pigs.